Infectious Risks and Complications in Adult Acute Lymphoblastic Leukemia (ALL) Patients Receiving Blinatumomab. (4th October 2017) - So, Wonhee; Pandya, Shuchi; Quilitz, Rod; Greene, John
Abstract: Background: Blinatumomab (BLN) is an anti-CD19 immunotherapy approved for relapsed/refractory (R/R) B-cell ALL with significantly increased survival rate. While BLN showed lower rates of infection, neutropenia and mucosal barrier injury (MBI) as compared with chemotherapy, its infection risks are not well described. BLN may also cause cytokine release syndrome and hypogammaglobulinemia. A retrospective review of the infectious risks and complications of BLN was performed for strategic antimicrobial prophylaxis. Methods: All patients who received BLN for ≥7 days at an academic cancer center from May 2015 to April 2017 were included. Patient characteristics pertinent to infectious risks and complications were examined. Results: Twenty patients with refractory (25%), relapsed (70%), or remitted (5%) B-ALL who received a total of 35 cycles were included. A median of 2 previous chemotherapies were given (range 1–7). Ten of the 35 cycles were interrupted, none of which were due to infections except in a patient who had hypotension with mild ground glass pneumonia. Twenty-six infections (n ) were observed with lower respiratory (9), gastrointestinal (6), and bacteremia (5) being most common. Four patients had nodular, probable mold pneumonia, 3 of which were newly developed on BLN. Compared with all patients, these patients had significantly lower absolute neutrophil count (ANC) on the first day of BLN (1897 vs. 208/µL, P = 0.045) and prolonged days of ANC <100/µL (3 vs. 8 days, P = 0.047). Among the four bacteremic patients, two patients received cytotoxic chemotherapy ≤ 3 days of the last BLN; 1 patient was discharged with no antibacterial since ANC recovered to >500/µL, but developed Pseudomonal bacteremia in a week with ANC 100/µL. There was one 30-day mortality (noninfectious). Two patients were sent to hospice care <30 days of BLN with progressive disease, one of who also had infectious complications. Conclusion: Despite lack of MBI and mild neutropenia by BLN, host factors (e.g., duration and degree of neutropenia/lymphopenia, stage of ALL, chemotherapy pre- and post-BLN) play a key role in this population and should be considered in designing anti-mold coverage. In R/R disease, ANC should be monitored closely both inpatient and outpatient as neutropenia can worsen post BLN compounded by disease and other chemotherapy. Disclosures: All authors: No reported disclosures.